Pengaruh Kualitas Pelayanan dan Persepsi Kewajaran Tarif terhadap Minat Kunjungan Ulang Pelanggan UPT Laboratorium Kesehatan Daerah - Ratna Yunita; Sri Rahayu; Rifda Fitrianty (BISMA : Business and Management Journal, 2026)
This study examines the simultaneous effects of service quality and perceived tariff fairness on customer revisit intention at a public health laboratory. Grounded in service-dominant logic and social equity theory, the research addresses a critical gap in public service marketing literature regarding hybrid governance institutions that blend commercial revenue mechanisms with welfare-oriented missions. Using an explanatory quantitative design, primary data were collected through structured questionnaires administered to customers of a regional public health laboratory operating under the Badan Layanan Umum Daerah framework in Gresik Regency. Multiple regression analysis revealed that both service quality and perceived tariff fairness significantly and positively influenced revisit intention, with the model explaining a substantial proportion of the variance. Notably, service quality exhibited a marginally stronger predictive power than tariff perception, suggesting that process experience outweighs cost considerations in shaping behavioral loyalty within preventive healthcare settings. These findings contribute to public service management theory by validating the co-existence of market and welfare logics in citizen decision-making and offer practical guidance for tariff policy formulation and service quality enhancement in publicly governed health laboratories.